PENILAIAN TERHADAP KUALITAS RUANG PUBLIK PADA KAWASAN GEDUNG KESENIAN DR IR. SOEKARNO DI PERKOTAAN NEGARA, JEMBRANA - Ni Nyoman Ayu Trisnowulan Rayadi Putri; I Made Gde Sudharsana; Wahyudi Arimbawa (UNHI PRESS, 2021)
The availability of public space is a must for a city. Public space serves as a place for people to meet, gather and interact, whether for religious purposes, trade or building government. This study aims to assess the quality of public space in the area of ​​the Gedung Kesenian Dr. Ir. Soekarno, Jembrana Regency. This research uses the approach of Carr's (1992) public space theory about aspects of forming the quality of public space which consists of 3 aspects, namely aspects of needs, aspects of rights, and aspects of meaning. The quality value is set in four types, namely good, sufficient, less good, and not good. The range of values ​​as a benchmark for the quality of public space is calculated by multiplying the maximum number of values ​​for each item on the question item by the weight of each sub-factor. The results showed that based on the measurement of the quality of the public space, it was found that the quality of the public space in the Dr. Art Building area. Ir. Soekarno is in the good category. Aspect value of needs (needs) obtained is 71.07 meaning good category. For the rights aspect, it got a score of 40.87 in the good category. Meanwhile, for the meaning aspect, the public space of the Dr. Art Building area. Ir. Soekarno got a score of 15.88 with a fairly good category. Overall, based on the results of data interpretation and analysis, it was concluded that the Dr. Ir Soekarno Art Building Area can be said to be a good quality public space.